A Meeting Place for Urban Slaves in Eighteenth-Century Rio de Janeiro. (3rd May 2016) - Lima, Tania Andrade
Abstract : This study presents the results of archaeological excavations undertaken in an urban site located on the Rua da Assembleia in the center of Rio de Janeiro, one of the city's oldest areas of occupation. Investigations uncovered an area used to dump waste materials and a water well made with stones, dating to between the end of the seventeenth century and the first decades of the eighteenth century. This site was used to collect water that supplied the small urban nucleus existing at the time. The space was also employed to dump the waste collected from the nearby area. These tasks were carried out by enslaved laborers who visited the space frequently. As a result, the site became a place of sociability where enslaved Africans met to share experiences and negotiate their interests. This article interprets the site as a meeting point for urban slaves and presents their material evidence.